ANALISIS PRODUKSI DAN PEMASARAN JAGUNG DI DESA LABUAN TOPOSO KECAMATAN TAWAELI KABUPATEN DONGGALA - Cristoporus Cristoporus; Sulaeman Sulaeman (Universitas Tadulako, 2009)
The objective of this study was to identify factors involving in production, marketing, margin of marketing and efficiency of marketing in Labuan Toposo, district of Tavaeli, Regency of Donggala. Samples were purposively chosen from a corn prroducer area. The total number of samples used were 39 people, consisted of 30 farmers, 4 collecting seller, and 5 retailing seller. Primary and secondary data were collected by direct interview with the farmers. The results indicated that all variables were significance at α 1% on corn production with F-test (156.37) > F-table (4.18). Partially, farm area size (X1) was highly significance with t-test (2.88)>t-table (2.78). Others variables shown significance were seed (X2) with t-test (2.36) > t-table (2.06) and manure (X4) with t-test (2.41)>t-table (2.06). The only variable shown not significance was employer (X3) with t-test (1.74)>t-table (2.06). Marketing analysis showed that type one marketting channel which has margin of IDR 250 was as followed farmer, collecting seller, and consumer, respectively. It is more efficient than type two channel: farmer, collecting seller, retail seller, and consumer, respectively, having margin of IDR 750.